Population Pharmacokinetic Modeling and Simulation of TQ-B3101 to Inform Dosing in Pediatric Patients With Solid Tumors - Yang, Fen; Wu, Huali; Bo, Yunhai; Lu, Ye; Pan, Hong; Li, Su; Lu, Qin; Xie, Simin; Liao, Harry; Wang, Bing (Frontiers in Pharmacology, 2022)
Abstract Background TQ-B3101 is a novel kinase inhibitor currently in development for the treatment of advanced malignant tumor and relapsed or refractory ALK-positive anaplastic large cell lymphoma. Methods A population pharmacokinetic model was developed using data collected from a Phase 1 study and a Phase 2 study to characterize the pharmacokinetic of TQ-B3101 and its active metabolite (TQ-B3101M). The final model was used to optimize dosing of TQ-B3101 for pediatric patients (6-<18 years) with anaplastic large cell lymphoma. Results The pharmacokinetic of TQ-B3101 and TQ-B3101M was adequately described by a 1-compartment model with first-order absorption and elimination for parent drug coupled with a 2-compartment model with time-dependent clearance for the metabolite. The clearance of TQ-B3101M decreased over time with a maximum fractional reduction of 0.41. The estimated apparent clearance and apparent volume of distribution of TQ-B3101 were 2850 L/h and 4200 L, respectively. The elimination half-life of TQ-B3101 was 1.0 h. The distribution and elimination half-lives of TQ-B3101M at steady state were 4.9 h and 39.4 h, respectively. The projected exposure of TQ-B3101M in virtual pediatric population following the body surface area tiered dosing regimen is similar to that in children pediatric patients after the recommended pediatric dose of crizotinib (280 mg/m2 twice daily), an analog of TQ-B3101M. Conclusions A population PK model was developed to provide optimal dose of TQ-B3101 for further development of TQ-B3101 in pediatric patients with anaplastic large cell lymphoma.